Seismic micro-zoning in the alpine valleys and local application in urban planning regulations - Stéphane Cartier (Revue de Géographie Alpine)
Management of earthquake risks in the sedimentary valleys of the Alps depends on the ability to transcribe scientific knowledge obtained from micro-zoning into urban planning regulations. France, Italy, Slovenia and Switzerland are working with new European codes, and within their respective political contexts, to improve earthquake safety on the basis of enhanced input on local geological conditions and vulnerability levels.